2021
DOI: 10.1038/s41467-021-25329-5
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembling human heart organoids for the modeling of cardiac development and congenital heart disease

Abstract: Congenital heart defects constitute the most common human birth defect, however understanding of how these disorders originate is limited by our ability to model the human heart accurately in vitro. Here we report a method to generate developmentally relevant human heart organoids by self-assembly using human pluripotent stem cells. Our procedure is fully defined, efficient, reproducible, and compatible with high-content approaches. Organoids are generated through a three-step Wnt signaling modulation strategy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
169
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(245 citation statements)
references
References 92 publications
5
169
0
Order By: Relevance
“…These ECs expressed the EndoEC markers NFATC1 and NPR3 , and their transcriptomic profiles were comparable with human umbilical vein endothelial cells (HUVECs) and human cardiac microvascular endothelial cells (HCMECs). Consistently, Lewis-Israeli et al also identified CMs, ECs, and Fbs in their organoids [ 20 ]. We also developed heart organoids with the three major cardiac cell types [ 28 ].…”
Section: The Anatomical Pattern Of Cardiac Cellsmentioning
confidence: 63%
See 3 more Smart Citations
“…These ECs expressed the EndoEC markers NFATC1 and NPR3 , and their transcriptomic profiles were comparable with human umbilical vein endothelial cells (HUVECs) and human cardiac microvascular endothelial cells (HCMECs). Consistently, Lewis-Israeli et al also identified CMs, ECs, and Fbs in their organoids [ 20 ]. We also developed heart organoids with the three major cardiac cell types [ 28 ].…”
Section: The Anatomical Pattern Of Cardiac Cellsmentioning
confidence: 63%
“…However, lumen formation does not seem to rely on the EndoECs, as the lumen can still form when the EndoECs developed on the outer organoid surface after VEGF treatment [ 27 ]. Lewis-Israeli et al and our study also generated organoids with chamber-like structures, and these chambers also developed independently from the EndoECs [ 20 , 28 ]. As chamber formation in the current organoids does not go through the same process as in vivo heart lumen development, there is limited value in modeling human heart lumen formation under normal and diseased conditions using organoid cultures.…”
Section: Heart Lumen Developmentmentioning
confidence: 97%
See 2 more Smart Citations
“…The advent of organoids is considered a major breakthrough in stem cell research and has enabled advancements in the applications of human iPSC for disease modelling. Human heart organoids provide an in vitro model of cardiac development and congenital heart disease ( Lewis-Israeli et al, 2021 ), inner ear organoids have been generated for modelling deafness ( Romano et al, 2021 ), airway epithelial cell organoids are frequently used in lung research ( Eenjes et al, 2021 ), intestinal organoids enable in vitro investigations of gut pathology ( Puschhof et al, 2021 ), and it is even possible to derive sensorimotor organoids capable of forming neuromuscular junctions ( Pereira et al, 2021 ).…”
Section: Brain Organoid Models Of Parkinson’s Diseasementioning
confidence: 99%